124k views
3 votes
What is the simplest form of this expression?
-(х – 2)(3х2 + 4х-5)

What is the simplest form of this expression? -(х – 2)(3х2 + 4х-5)-example-1

2 Answers

3 votes
C.
(-x+2) (3x^2 + 4x-5)
-3x^3 -4x^2 + 5x (distributing (-x) into everything)
6x^2 + 8x -10 (distributing 2 into everything)
-3x^3 +2x^2 +13x - 10... (adding like terms)
Answer choice C
User LukasKawerau
by
5.4k points
3 votes

Answer:

C

Explanation:

3x^2 * -x =-3x^3

3x^2 * 2. =6x^2

4x* -x =-4x^2

4x * 2 = 8x

-5 * -x = 5x

-5 * 2 = -10

6x^2 + -4x^2 = 2x^2

8x+5x = 13 x

Ans: -3x^3 + 2x^2 + 13x -10

User MLSC
by
4.7k points